2020
DOI: 10.1093/schbul/sbz134
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Interventions for Cognitive Impairments in Psychosis: A Systematic Review and Meta-Analysis

Abstract: Abstract Objective Cognitive compensatory interventions aim to alleviate psychosocial disability by targeting functioning directly using aids and strategies, thereby minimizing the impact of cognitive impairment. The aim was to conduct a systematic review and meta-analysis of cognitive compensatory interventions for psychosis by examining the effects on functioning and symptoms, and exploring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…Integrated models of rehabilitation, such as the Boston Psychiatric Rehabilitation Approach [BPRA; (35)(36)(37)] and the Strengths model (38), provide tools to gain insight into and work toward recovery goals. Additionally, rehabilitation interventions that focus on recovery in specific (life)domains are available, ranging from cognitive remediation programs with a focus on functional impairment due to cognitive impairments [e.g., (39,40)], lifestyle interventions [e.g., (41,42)], and interventions aiming for recovery in the domain of work/school such as supported employment [e.g., (43)] or supported education programs [e.g., (44)]. In the last decade, user-led/user-developed interventions have gained increasing ground, such as Wellness Recovery and Action Planning [WRAP; (45)], "Recovery is up to you" (46), and Toward Recovery, Empowerment and Experiential Expertise (47).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated models of rehabilitation, such as the Boston Psychiatric Rehabilitation Approach [BPRA; (35)(36)(37)] and the Strengths model (38), provide tools to gain insight into and work toward recovery goals. Additionally, rehabilitation interventions that focus on recovery in specific (life)domains are available, ranging from cognitive remediation programs with a focus on functional impairment due to cognitive impairments [e.g., (39,40)], lifestyle interventions [e.g., (41,42)], and interventions aiming for recovery in the domain of work/school such as supported employment [e.g., (43)] or supported education programs [e.g., (44)]. In the last decade, user-led/user-developed interventions have gained increasing ground, such as Wellness Recovery and Action Planning [WRAP; (45)], "Recovery is up to you" (46), and Toward Recovery, Empowerment and Experiential Expertise (47).…”
Section: Introductionmentioning
confidence: 99%
“…procedural memory) or by implementing environmental supports (i.e. alarm reminders, checklists) that sustain independent living and autonomy [12][13][14].…”
mentioning
confidence: 99%
“…Individualized cognitive remediation and concrete objectives on people's everyday complaints may be an effective alternative to obtain a meaningfully lasting transfer of training to daily life [15]. Importantly, it has been suggested that compensatory approaches are generally more e cient than restorative ones and more easily generalized to daily activities [14].…”
mentioning
confidence: 99%
See 2 more Smart Citations